Comparative study of apical sealing in root canals filled by the Single Cone Protaper and Termoplastic TC Sytem techniques - Key Fabiano Souza Pereira; Paula Tereza Vardasca de Oliveira; Ana Camila Ferreira da Silva Queiroz; Pedro Gregol da Silva; João Luís Néri Damasceno (Faculdade São Leopoldo Mandic, 2008)
Objective: To evaluate in vitro the apical microleakage of different root canal filling techniques: ProTaper single cone and TC System without the use of a master gutta-percha point. Methods: For the present experiment, twenty-four disto-buccal roots obtained from maxillary molars were prepared using the ProTaper system (Dentsply-Maillefer, Suíça) and randomly divided in two groups. Group I was filled according to the single cone technique, while in Group II the TC system was used without a master gutta-percha point. AH Plus (Dentsply, Rio de Janeiro, Brasil) was used as root canal sealer in both groups. After making the roots impermeable with nail varnish, they were immersed in Indian ink and submitted to vacuum for 30 min, remaining in the marker for seven days. After this period, the samples were decalcified, dehydrated, clarified and the infiltration levels were observed under a stereoscopic loupe. Results: Statistical analysis revealed no significant differences between the evaluated techniques. Conclusion: Both techniques evaluated in the present study were unable to avoid apical microleakage, and showed similar results.